What makes national sport federations consider environmental sustainability? A conceptual framework on the agenda setting process based on a multiple case study - Sarah Piller; Siegfried Nagel (Bern Open Publishing, 2024)
Introduction In Europe, more than 60 million people practice sport in a club. Through the consumption behaviour of this large number of sport club members, organised sport not only has positive impacts, but can be deleterious to the environment, for example through travel behaviour or the destruction of natural habitats caused by sport activities and required infrastructure (McCullough et al., 2020). National sport federations, which represent sport clubs and engage in sport policy issues, could be crucial when it comes to taking measures concerning the environmental sustainability of and through organised sport. However, sport federations are traditionally committed to the interests of their members and sport as their core business (Thiel & Mayer, 2009). Therefore, this study addresses the extent to which environmental policies are set on agendas in national sport federations and which drivers are relevant for the agenda setting of such policies. Methods To gain a comprehensive and in-depth understanding of these questions, we conducted an explorative qualitative multiple case study with eight Swiss sport federations. To investigate the agenda-setting process in sport organisations, we employed the multiple streams approach by Kingdon (1984). Results The developed conceptual framework shows that whereas nature conservation policies were primarily driven by national regulations, climate protection policies were pushed by engaged functionaries of the federations. Functional issues (as opposed to normative arguments), sponsor and member interests, practices of other federations and societal developments could further facilitate or impede the agenda setting of all types of environmental policies. Discussion/Conclusion This study provides valuable insights into the drivers of the agenda setting of environmental policies in national sport federations. Furthermore, it outlines the fit and limitations of the multiple streams approach according to Kingdon (1984) to explain agenda setting processes in national sport federations and extends it by external factors to gain a more holistic perspective of the phenomenon. Understanding drivers in the agenda setting of environmental policies in national sport federations is especially important because it is a prerequisite for the subsequent decision making and implementation of such policies and can help to shape the response of the organised sport to environmental challenges. References Kingdon, J. W. (1984). Agendas, alternatives, and public policies. Little Brown and Co. McCullough, B. P., Orr, M., & Watanabe, N. M. (2020). Measuring externalities: The imperative next step to sustainability assessment in sport. Journal of Sport Management, 34(5), 393-402. https://doi.org/10.1123/jsm.2019-0254 Thiel, A., & Mayer, J. (2009). Characteristics of voluntary sports clubs management: A sociological perspective. European Sport Management Quarterly, 9(1), 81-98. https://doi.org/10.1080/16184740802461744